2007
DOI: 10.1111/j.1469-7580.2007.00773.x
|View full text |Cite
|
Sign up to set email alerts
|

The development of the neural crest in the human

Abstract: The first systematic account of the neural crest in the human has been prepared after an investigation of 185 serially sectioned staged embryos, aided by graphic reconstructions. As many as fourteen named topographical subdivisions of the crest were identified and eight of them give origin to ganglia (Table 2). Significant findings in the human include the following. (1) An indication of mesencephalic neural crest is discernible already at stage 9, and trigeminal, facial, and postotic components can be detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(109 citation statements)
references
References 77 publications
2
100
0
5
Order By: Relevance
“…The important structure during the development of the nervous system is the neural crest which gives rise to variety of derivatives including the spinal and cranial ganglia [28]. In human embryos, the neural crest is indicated first at stage 9 in mesencephalic neuromere.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The important structure during the development of the nervous system is the neural crest which gives rise to variety of derivatives including the spinal and cranial ganglia [28]. In human embryos, the neural crest is indicated first at stage 9 in mesencephalic neuromere.…”
Section: Discussionmentioning
confidence: 99%
“…The sensory nuclei of the cranial nerves develop in the common afferent tract [6,11,20,28]. The motor nucleus of the facial nerve in all investigated stages is medially to the abducent nucleus in the future dorsomedial nuclear column.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that in rats the cranial ganglia and nerves were HNK-1 positive (Louryan et al, 1996;Nagase et al, 2003). Thus, in human (O'Rahilly and Mü ller, 2007) and chicken embryos (Shigetani et al, 2008), it has been reported that the trigeminal ganglion originated from the neural crest and from the trigeminal placode (Knabe et al, 2009). Probably, the parts of the trigeminal ganglion that originate from the trigeminal placode correspond to the parts that were HNK-1 negative.…”
Section: Juxta-oral Organ In Rat Embryomentioning
confidence: 99%
“…14 It is found that frontal, parietal, squamous part of temporal bones and upper part of occipital squama are developed from neural crest. 15 Neural tube defects occur due to failure of mutual induction of germ layers in related sequence. Disturbances of inductive events involved in primary neurulation leads to various errors of neural tube closure followed by alterations of axial skeleton as well as overlying meningovascular and dermal coverings.…”
Section: However Nakatsu Et Al (2000) Observed 3 Sites Ofmentioning
confidence: 99%